HuR Reduces Radiation-Induced DNA Damage by Enhancing Expression of ARID1A - Andrade, Daniel (Cancers (Basel), 2019)
Tumor suppressor ARID1A, a subunit of the chromatin remodeling complex SWI/SNF, regulates cell cycle progression, interacts with the tumor suppressor TP53, and prevents genomic instability. In addition, ARID1A has been shown to foster resistance to cancer therapy. By promoting non-homologous end joining (NHEJ), ARID1A enhances DNA repair. Consequently, ARID1A has been proposed as a promising therapeutic target to sensitize cancer cells to chemotherapy and radiation. Here, we report that ARID1A is regulated by human antigen R (HuR), an RNA-binding protein that is highly expressed in a wide range of cancers and enables resistance to chemotherapy and radiation. Our results indicate that HuR binds ARID1A mRNA, thereby increasing its stability in breast cancer cells. We further find that ARID1A expression suppresses the accumulation of DNA double-strand breaks (DSBs) caused by radiation and can rescue the loss of radioresistance triggered by HuR inhibition, suggesting that ARID1A plays an important role in HuR-driven resistance to radiation. Taken together, our work shows that HuR and ARID1A form an important regulatory axis in radiation resistance that can be targeted to improve radiotherapy in breast cancer patients.